2019
DOI: 10.1016/j.eururo.2018.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Antifibrotic Synergy Between Phosphodiesterase Type 5 Inhibitors and Selective Oestrogen Receptor Modulators in Peyronie's Disease Models

Abstract: Background: Peyronie's disease (PD) is a fibrotic disorder of the penile tunica albuginea, characterised by the formation of a localised fibrous plaque that can lead to deformity and erectile dysfunction. Nonsurgical therapeutic options for PD are limited in efficacy and safety. Myofibroblasts are key cells in the pathogenesis of PD, and inhibition of myofibroblast transformation has been suggested as a therapeutic option. Objective: To identify potential drugs using a novel phenotypic assay and then to test t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 41 publications
2
57
1
1
Order By: Relevance
“…In PD, the origin of MFBs is ill‐investigated; nonetheless, it seems that TGF‐β1 is the common denominator. Thus, inhibition of TGF‐β1 signalling would probably impair MFB formation and subsequent fibrosis, regardless of the MFB origin, especially because TGF‐β1 has been previously described as a main driver of MFB transformation in PD , to the extent that the most widely used animal model of the disease is based on injection of the cytokine .…”
Section: Discussionmentioning
confidence: 99%
“…In PD, the origin of MFBs is ill‐investigated; nonetheless, it seems that TGF‐β1 is the common denominator. Thus, inhibition of TGF‐β1 signalling would probably impair MFB formation and subsequent fibrosis, regardless of the MFB origin, especially because TGF‐β1 has been previously described as a main driver of MFB transformation in PD , to the extent that the most widely used animal model of the disease is based on injection of the cytokine .…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, we acknowledged a growing interest in basic and translational research on PD pathogenesis, including the developing of the first in vitro cell culture models [10,11]. Even though, little progresses have been made towards further elucidating the real etiology of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that the combination of sildenafil and CCH is better in improving PD curvature associated with ED than CCH alone 40 . Another study on a rat model of PD had shown that vardenafil and tamoxifen may reduce myofibroblast alteration, collagen fiber contraction, and production of extracellular matrix in a synergistic manner 41 . Human studies that investigated the importance of chronic use of PDE5Is to treat penile deformity related to PD are rare; however, based on their wide availability and safety, the utilization of PDE5I in combination therapy for PD seems reasonable 42 …”
Section: Methodsmentioning
confidence: 99%